A formação do ator para uma atuação polifônica: princípios e práticas - Ernani de Castro Maletta (2005)
The actor’s multiple education is the objective of the present research, keeping in mind that Theatre as a type of Art that encompasses all the artistic languages, demands an intersemiotic. interdisciplinary and thorough preparation. When stating that each of the-referred languages represents a discursive instance, the intention was to point out that the actor, beside being one of the voices of the scenic scores, when acting, shall consciously incorporate and appropriate the other voices that express those various and simultaneous discourses pertaining to the scenic act: the voice of other actors, the author's voice, the director's, the music director's, the bodywork director's, the set designer’s, wardrobe designer's, light technicians* and all others responsible for the creation of the performance. Thus, the actor builds a discourse in which multiple, counterpointing voices provide the base for the actor's performance, which will be polyphonic. Based on these premises, we have investigated the principles and practices that are able to orient guide such preparation. Our option was to ground the debate starting from the reconstruction and analyses of the researcher’s own experiences which have always focused the polyphonic acting. With that in mind, the researcher's professional route was recomposed by counterpointing various voices — from teachers, theatre theorists and consecrated actors who have been in charge of educating the actor, and who have been treading on equally polyphonic paths. As a result, the research highlights points out the principles suggested by the various practices submitted to analyses, which. lead. mainly, towards the indispensability of encompassing fundamental concepts and techniques coming from the various artistic languages, unveiling, consequently. the required appropriation, in a conscious way, of those appropriated languages. To do so, the actor's education is to be oriented by interdisciplinary workshops which. beside focusing the apprentice of the language fundaments, allow that this actor, instead of becoming a mere spokesman of incorporated discourses. consciously take over their appropriation, counterpointing multiple voices when creating a discourse that structures his/her polyphonic acting.